Investigation of amoeboid cells in oral squamous cell carcinoma and their participation on metastasis - Ortiz, Rafael Carneiro (2022)
Oral squamous cell carcinoma (OSCC) is a typically aggressive malignant tumor from the subgroup of head and neck cancers. Although there is an improvement in OSCC treatment, the 5-year survival rate remains unsatisfactory, mostly related to metastasis, a process increasingly associated to the presence and maintenance of cancer stem cells (CSC) subpopulation. CSCs exhibit higher rate of migration and metastatic potential compared to other tumor cells, and are able to undergo either epithelial-mesenchymal transition (EMT) or amoeboid transition to become more invasive and resistant, respectively. Therefore, understanding how CSCs act during tumor progression and its relationship with amoeboid/EMT transitions according to tumor site could be clinically relevant. Based on that, this study aimed to identify putative biomarkers of CSC, EMT and amoeboid phenotypes involved with poor prognosis in OSCC. Our findings demonstrated that higher immunopositivity of the CSCs markers ALDH1 and CD44, in contrast to decreased BMI-1 immunoexpression, might be considered predictors of metastasis. In addition, CD44high immunostaining was specifically associated with lymph node capsular extravasation, while E-cadherinlow worsen 5-years OSCC survival rates. Positives correlations among CD44 and BMI-1 with E-cadherin indicate their possible biological relationship during OSCC progression. Considering the amoeboid genes, PRRX1 immunopositivity was associated with lymph nodes metastasis, while HOPXhigh was associated with increase on the intensity of the peritumoral inflammatory infiltrate, both in central and ITF of non-metastatic tumors. In vitro, PRRX1 was upregulated in CA1 amoeboid cells compared to parental CA1, as well as to both parental and amoeboid LUC4 cells. Of note, the presence of CTCs was correlated with distant metastasis in OSCC patients. In summary, our results suggested that putative CSC markers ALDH1, CD44, p75NTR, and BMI-1, as well as E-cadherin, immunoexpression are associated with poor prognosis in a specific expression level and tumor site manner and, could be used as a panel for OSCC prognosis. Our data also propose that the increased immunoexpression of amoeboid protein PRRX1 could be associated with the amoeboid phenotype. Additionally, the correlation of CTCs with distant metastasis could represent an important role in the establishment of metastasis by CTCs related to the amoeboid phenotype. Although this link is still speculative in OSCC, it is possible to imply that amoeboid and CTCs phenotypes could be used to predict poor prognosis/oral cancer progression and metastasis in OSCC.